Adopting and Sustaining Microservice-Based Software Development. - Vitharana, Padmal; Daya, Shahir A. (Communications of the ACM, 2024)
This article provides an overview of microservice-based software development (MS) which has increased in popularity as an alternative to monolithic architecture due to its ability to map dynamic business changes to IT/IS changes more effectively. MS architectures, composed of smaller, independently deployable services, offer benefits such as scalability, ease of requirement changes, and technology innovation. However, adopting and sustaining MS development presents challenges that are highlighted in this article, including technical and organizational hurdles, that need to be understood and managed to fully realize the potential benefits.